Onomastics of the dishes of Peruvian food from the perspective of cognitive linguistics - Loayza-Maturrano, Edward Faustino (2021)
The objective of this article is to determine, through the analysis of the types of metaphors and conceptual metonymies, the specific cognitive procedures used in the naming of Peruvian food dishes; all based on the theory of cognitive linguistics. The research method is qualitative-hermeneutical of the critical discourse analysis type supported by the theory of cognitive linguistics. The results show that the names of Peruvian food dishes present metaphorical processes of two types: single metaphor and multiple metaphors. Likewise, the names of Peruvian food dishes present two metonymic processes: single metonymy and multiple metonymies. The existence of interaction between metaphor and metonymy in the process of naming dishes is also determined. The conclusion of the study explains that the individual when naming the dishes shows three tendencies in onomastic creation: tendency of cultural choice, tendency of personal experience and pragmatic tendency.